Social Media Ethics in the Post-Truth Era: Ibn Miskawaih’s and Mohammed Arkoun’s Thought on Digital Literacy - Ihsyan Wahyudi (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study aims to examine ethical challenges posed by social media practices in the post-truth era through an integrative analysis of Ibn Miskawaih’s virtue ethics and Mohammed Arkoun’s critical Islamic thought. The post-truth condition—marked by the primacy of emotions, personal beliefs, and algorithmic mediation over objective facts—has significantly undermined the authority of truth in digital communication. Phenomena such as ideological echo chambers, disinformation, and uncritical content circulation necessitate a robust ethical framework that extends beyond technical digital literacy. Employing qualitative library research with a philosophical approach, this study conducts conceptual and comparative analyses of Ibn Miskawaih’s Tahdhīb al-Akhlāq and Arkoun’s key writings, supported by contemporary literature on post-truth discourse and digital ethics. The findings reveal that Ibn Miskawaih’s emphasis on moral equilibrium, justice, truthfulness, self-discipline, and wisdom provides a virtue-based foundation for ethical digital behavior. Complementarily, Arkoun’s advocacy of critical reason, epistemic openness, pluralism, and resistance to ideological closure offers essential tools for confronting misinformation and extremism in digital spaces. This study argues that synthesizing these two intellectual traditions yields an ethical model that reinforces critical digital literacy, fosters responsible social media engagement, and contributes to the cultivation of a morally grounded public sphere in the post-truth era.